O sujeito no armário em face do "abjeto" objeto de desejo: a dinâmica do outing na “narrativa de revelação” de uma telenovela global - Assis Neto, Pedro Vicente de (2017)
This research have its central issue on the matter of visibility conferred to gay characters of soap operas that find themselves "coming out of the closet", that is, when they open to the public their sexual orientation. It is placed at a television context, where performances of homo-oriented relations were, historically, marginalized and had to adjust to a society marked by heteronormativity. To this disciplinary and hierarchical model of sexes and genders, some thoughts are considered, without losing sight of them as discourses that seek to criminalize, moralize, pathologize, and make these dissident masculinities invisible. Therefore it is yet to be investigated if the so-called "narratives of revelation" and their representations that emerge from brazilian television shows are positive and creative affirmations of their own identity positions or are reinforcing clichés based on a series of stigmas and prejudices about them. The soap opera "Babylon" is taken as the case of study, analyzing the discourses produced for its scenes and dialogues that are focused on the characters of Ivan and Sergio, in order to reconfigure the path that leads from subjectivity, condensed by the closet entity, to the reinvention of oneself. Based on the encounter of these two characters mentioned throughout the narrative, there will be taken in account markers of social, economic, ethnic and generation differences. By inciting those matters, this research uses "depth hermeneutics" as it's method, since it is a "three-phase procedure", which contemplates the conditions of production, construction and reception of the messages that are being sent by the discourses produced over these characters. Hence it matters how much, in this particular context, this gay couple was crossed by outer effects towards its creation and also, to what price they could express in words and through body language what they felt for each other amid censorship tactics from the tv show author and amid boycotts from part of the audience.